Peran Ukuran Perusahaan Sebagai Variabel Moderasi pada Pengaruh Good Corporate Governance dan Corporate Social Responsibility terhadap Nilai Perusahaan: Studi Empiris pada Perusahaan Sub Sektor Transportasi dan Logistik Yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2019-2023 - Egariska Sari; Sri Rahayu (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
This study was conducted to examine the influence of GCG and CSR on company value with company size as a moderation variable. The sample selection technique in this study uses the purposive sampling method and was obtained from 20 transportation and logistics companies listed on the Indonesia Stock Exchange for the 2019 – 2023 period. The data analysis used in this study is multiple linear regression analysis using SPSS software version 25. Based on the results of the study, it can be concluded that managerial ownership and institutional ownership have no effect on the company's value, while the independent board of commissioners and CSR have a positive effect on the company's value. The size of the company is able to moderate managerial ownership and institutional ownership on the value of the company, but it is not able to moderate the influence of the independent board of commissioners and CSR on the value of the company. It is recommended that researchers further add other factors that affect the value of companies, as well as expand the scope of companies so that the sample will be more and more.